2016
DOI: 10.3414/me14-01-0106
|View full text |Cite
|
Sign up to set email alerts
|

Self-assessment of Rheumatoid Arthritis Disease Activity Using a Smartphone Application

Abstract: The results of this feasibility study indicated that the DAS28 predictive model can longitudinally predict DAS28 and may be an acceptable and useful tool for assessment of RA disease activity for both patients and healthcare providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The app has the potential for data collection at a higher frequency (eg, multiple points per day) than would be logistically possible in standard clinical studies; therefore, it can provide a more holistic view of disease exacerbation and remission. Furthermore, a previous study demonstrated that capture of Disease Activity Score in 28 joints data using a dedicated smartphone app correlated well with monthly clinical assessments of RA disease activity [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The app has the potential for data collection at a higher frequency (eg, multiple points per day) than would be logistically possible in standard clinical studies; therefore, it can provide a more holistic view of disease exacerbation and remission. Furthermore, a previous study demonstrated that capture of Disease Activity Score in 28 joints data using a dedicated smartphone app correlated well with monthly clinical assessments of RA disease activity [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, monitoring the impact of physical activity on cardiovascular health, by gathering objective data relating to patient mobility and activity levels through the use of the integral smartphone global positioning system, was shown to be successful [ 12 ]. An attempt to capture data relating to gait analysis in patients with RA has been reported, but this method awaits full validation [ 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Capitalizing on the popularity of smartphone-based entertainment in adolescents, health apps may represent an important means of increasing self-management through remote monitoring and access to information [ 33 - 36 ]. For example, health management behaviors can be integrated with daily activities, using technologies that can track information “on the go.” Apps used to monitor symptoms remotely also have considerable potential in helping HCPs deliver safe and timely health care, as it provides more accurate and frequent reports of health status compared with using paper diaries [ 37 - 39 ]. Reliable and secure electronic data collection of symptoms and emotions not only benefits clinical assessments, but it is also an established method for validly collecting daily data in research as well [ 40 - 43 ] and can help advance knowledge on factors influencing disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a feasibility study of a smartphone application for sleep apnea patients [27] demonstrated good feasibility with > 60% of participants completing the daily questionnaire, > 65% of the study time, and with a 94% satisfaction rates. Another small 3-month feasibility study in rheumatoid arthritis [28] measured the self-assessment of daily disease activity using a smartphone application. The vast majority of these participants (~ 88%) had no issues reporting their daily symptoms, and all were confident sharing their information.…”
Section: Discussionmentioning
confidence: 99%